The Snout Of Cricosaurus Araucanensis: A Case Study In Novel Anatomy Of The Nasal Region Of Metriorhynchids - Herrera, Laura Yanina (2013)
Metriorhynchids are the only crocodyliforms adapted to pelagic marine life. Snout natural endocasts of the Tithonian (Late Jurassic) metriorhynchid Cricosaurus araucanensis indicated that skeletal changes defining the peculiar metriorhynchid body plan were coupled with changes of the soft cephalic anatomy such as the enlarged salt glands and restructuring of the paranasal sinus system. Seven new natural endocasts of the snout and a 3-D reconstruction of C. araucanensis are described. Data from these casts and the reconstruction are congruent, and they are combined into an accurate reconstruction that improves our knowledge of the pre-orbital anatomy. The olfactory tract, bulbs, olfactory nasal region and the anterior extension of the antorbital sinus within the maxilla are recognized. Osteological correlates of the salt gland body are also proposed. Palaeobiological inferences are erected based on the integration of natural endocasts and 3-D reconstruction data. It is proposed that C. araucanensis nasal salt glands were highly vascularized with a blood supply comparable with those of extant marine birds. Reduced olfactory bulbs and olfactory nasal region indicate that the aerial olfaction, differing from extant crocodilians, was not well developed.